Separator membranes for lithium-sulfur batteries: design principles, structure, and performance - Gupta, Aritrajit; Sivaram, Swaminathan (Energy Technology, 2019)
Improvement in electrical energy storage systems is one of the most recent research topics of great academic and industrial interest. Lithium-sulfur (Li-S) battery systems offer a theoretical energy density an order of magnitude larger than the popular Li-ion batteries. The principle of working, inherent challenges in utilizing this system for commercial applications, and the various approaches taken to address these challenges are herein discussed in detail. The polysulfide shuttle effect is a major concern that deteriorates electrochemical performance in this system. In the recent past, electrodes have been intricately engineered to tackle this problem. However, more recently, the focus has shifted to the critical role of the separator. Modifying conventional separators or fabricating novel structures to enhance the cell performance appears to be a more feasible option. Some design principles that are critical to the functioning of a separator in Li-S batteries, namely physisorption, chemisorption, and electrostatic repulsion, are discussed. Many recent papers proposed novel cell configurations with specifically designed functional separators. These reports are classified according to three design principles, analyzed critically, and compared with a view to assess their relative merits and efficacy. Some thoughts on the future directions in the development of an efficient separator are described.
Keywords: lithium-sulfur batteries; polysulfides; rechargeable batteries; separators; shuttle effect